DESIGN OF FASHION-BASED TEACHING BOOKS INTERACTIVE E-BOOK IN THE LEARNING ERA BLENDED LEARNING - Erni, Erni; Rambe, Armaini; Januariansyah, Sapitri; Bahri, Halimul (Teunuleh Publisher, 2022)
Learning that takes place in the Fashion Design Education Study Program is of course related to practical learning in the field of fashion. In the practicum learning process, students need a high level of understanding to carry out every step of making a dress. Learning that is regulated by blended learning has various obstacles including; restrictions on the number of practicum classes in class, different levels of student understanding, mastery of sewing skills that are not the same, inadequate learning tools and also internet network disturbances during online learning. This study aims to design interactive e-books to support blended learning. An e-book is a book that is programmed into a computer so that it can visualize abstract material into a visual form that can be animated so that students are more interested in the learning process. The development of interactive e-book media uses a 4-D development model through 4 stages, namely the Define stage, the Design stage, the Development stage and the Disseminate stage. Data collection techniques using questionnaires and observation sheets. The results showed that the average practicality test results were in the practical category and the effectiveness test was in the good category.